Situation Report: Bulgaria, 17 July 1968 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Bulgarian Information Media on the Warsaw Meeting Party Development in the Province Drought Continues to Be a Problem for Agriculture Miscellaneous Venezuelan Economic Delegation in Bulgaria Romanian Official for Balkan Cooperative Visits Sofia Bulgarian Party Activists in Romania